Fluidity, Identity, and Organizationality: The Communicative Constitution of Anonymous - Dobusch, Leonhard; Schoeneborn, Dennis (Journal of Management Studies, 2015)
AbstractThis paper examines how fluid social collectives, where membership is latent, contested, or unclear, achieve ‘organizationality’, that is, how they achieve organizational identity and actorhood. Drawing on the “communicative constitution of organizations” perspective, we argue that the organizationality of a social collective is accomplished through ‘identity claims’ – i.e., speech acts that concern what the social collective is or does – and negotiations on whether or not these claims have been made on the collective's behalf. We empirically examine the case of the hacker collective Anonymous and analyse relevant identity claims to investigate two critical episodes in which the organizationality of Anonymous was contested. Our study contributes to organization studies by showing that fluid social collectives are able to temporarily reinstate organizational actorhood through the performance of carefully prepared and staged identity claims.